Impact of Great cormorant (Phalacrocorax carbo sinensis) on post-smolt survival of hatchery reared salmon (Salmo salar) and sea trout (Salmo trutta) - Gavell, Carolina (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
To compensate for the losses due to altered stream habitat large amounts of hatchery-reared Atlantic salmon (Salmo salar) and sea trout (Salmo trutta) are released into the Baltic Sea each year. During the last decades there have been an overall declining trend in the post-smolt survival of both hatchery reared and wild salmon in the Baltic Sea. During this period there has been a rapid increase of the piscivorous great cormorant (Phalacrocorax carbo sinensis) but also in the grey seal (Halichoerus grypus) population of the Baltic Sea. These two predators consume large amounts of fish in the Baltic Sea. This study investigated if the predation of great cormorants contributes significantly to the mortality of hatchery reared salmon and sea trout, together with the effects of the increasing grey seal population on hatchery reared salmon. Besides gut content analyses of cormorants, an index of return rate and post-smolt survival were estimated from data on salmon and sea trout smolt releases between 1989-2010 in river Dalälven, and the returning spawners from these releases. The dietary study was performed on cormorants nesting in the Sundsvall bay, where the stomachs of 183 cormorants were examined. The cormorants were culled as a protective measure both in direct relation to smolt release right outside Bergeforsen hatchery, and later in the season at Alnö, further out in the Sundsvall bay. The dietary study showed a high number of sticklebacks (Gasterosteidae) in cormorants from both areas. For cormorants culled near Bergeforsen hatchery salmonoids (Salmo spp.) had the highest relative biomass (68.18 %) and the highest frequency of occurrence (48.1 %). For cormorants culled at Alnö the predation on salmonoids were lower in comparison with other fish species, sticklebacks had the highest frequency of occurrence (67.2 %) and fourhorn sculpin (Triglopsis quadricornis) the highest relative biomass consumed (27.4 %). The estimated post-smolt survival of the Dalälven smolt did not differ from the overall estimates of ...